Theoretical Underpinnings vis - á - vis of Double Taxation Problem (Journal of Legal Studies, 2014)
The problem of international double taxation was highlighted in the judicial and economical literature, starting from 1990’s. Double taxation is a serious problem, especially regarding the construction of the so-called fiscal space in European Union. The problem of double taxation has two different dimensions: first, the so-called judicial double taxation which is seen as the situation in which two or multiple states have the subject of taxation the same contributor for the same income or capital; moreover, economical double taxation occurs in the situation in which two different persons are the subject of taxation for the same income or capital. In this article we provide a qualitative overview regarding the most important features of double taxation problems, with a special focus on European Union fiscal space.